The Reliability of AI in Medical Imaging: Separating Hype from Clinical Reality - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The Reliability of AI in Medical Imaging: Separating Hype from Clinical Reality The integration of Artificial Intelligence (AI) into medical imaging—enc...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care